ICE STORAGE CHARACTERISTICS OF CULTURED SILVER CARP - KUMAR, MONORANJAN; BASU, SUBRATA; HAZRA, A. (Journal of Indian Fisheries Association, 2015)
Cultured silver carp (Hypopthalmichthys molitrix 800-1000 g) was stored in ice (fish to ice ratio 1:1) in a plywood box insulated with one inch thick expanded poly styrene and subjected to detailed examination of quality by chemical, microbilogical and organoleptic evaluation at regular intervals to asses the storage life in good acceptable form. Alphaamino nitrogen, non-protein nitrogen and pH values showed no positive correlation as spoilage index. Total volatile base nitrogen was not high at the end of the storage period although the fish became unacceptable Â·during the period. There was steep decrease in total bacterial count during initial stages of storage and then incr-eased steadily on further storage. Organoleptic evaluation of raw and cooked meat revealed that fish was in good acceptable form upto 14 days in ice.